Effects of different types of protected fat on rumen metabolism, meat quality and metabolomics in dorper crossbred sheep - Behan, Atique Ahmed (2018)
The prilled fat, lecithinized prilled fat and calcium soap (calcium salts of palm fatty acids) are the extensively used rumen protected fats (RPF). These are used in ruminant diets to protect dietary lipids from rumen biohydrogenation and to prevent detrimental effects of high fats on rumen fermentation. Supplementation of the protected fats could improve in vitro and in vivo rumen metabolism, nutrient intake and digestibility, meat quality and metabolomics; and modify meat fatty acid profile. There is very limited number of studies in the literature discusses the use of RPF and their impact on performance, meat quality characteristics and fatty acid profile in sheep. However, the influences of RPF supplementation on rumen metabolism have been highly variable and inconsistent and their impacts on meat quality remain obscure. Therefore there is a need for specific studies to permit personalized decisions and informed choices in the utilization of protected fats. Thus, the present study was conducted to examine the effects of different types of protected fats on in vitro and in vivo rumen metabolism, nutrient intake and digestibility, serum biochemistry; meat quality and fatty acid profile and meat metabolomics in Dorper crossbred sheep. In vitro experiment was conducted using ruminal fluid from fistulated Dorper sheep. Treatment consisted of basal diet (70:30 concentrate to rice straw) with no added RPF (T1), basal diet plus prilled fat (T2), basal diet plus prilled fat with lecithin (T3) and basal diet plus calcium soap of palm fatty acids (T4). Completely randomized design (CRD) was followed. In vitro gas production, fermentation kinetics, in vitro dry matter digestibility (IVDMD), in vitro organic matter digestibility (IVOMD), rumen fermentation characteristics and apparent biohydrogenation of fatty acids were determined. The cumulative gas production and gas production kinetics were not affected by RPF. Prilled fat with lecithin increased IVDMD and IVOMD significantly. Metabolizable energy was not affected by addition of RPF. The RPF did not influence significantly pH, ammonia nitrogen, methane, VFA and molar proportion of VFA. However, the diet containing prilled fat with lecithin (T3) reduced acetate to propionate ratio, decreased methane numerically and increased biohydrogenation of C18:2n-6 and C18 UFA without disrupting rumen fermentation. For the in vivo experiment, 36 male Dorper crossbred sheep about 18 months of age were used to evaluate the effects of different protected fats on nutrient intake, nutrient digestibility, serum biochemistry, meat quality and fatty acids. The animals were fed with the four experimental diets for 90 days (including last 10 days for digestibility trial) and were slaughtered. The diets did not affect body weight (BW), feed conversion ratio (FCR) and feed efficiency. There was no significant difference (P>0.05) seen in the intake and digestibility of all nutrients except ether extract (EE) and crude fibre (CF). The rumen fermentation characteristics including pH, methane (CH4), VFA and molar proportions of VFA, acetate to propionate ratio differ significantly (P<0.05). The maximum CH4 reduction was observed in the diet T3 while T2 showed the least reduction. Concentration of ammonia nitrogen was not different significantly (P>0.05) among the treatments. Numerically the lowest total VFA concentration was seen in the diet prilled fat with lecithin (T3). Fatty acid profile of rumen digesta was significantly different for ΣSFA, ΣMUFA, ΣPUFA, Σn-3 and Σn-6. Neither the diet nor the sampling time influenced serum cholesterols (total, HDL, LDL and VLDL), triglycerides, glucose and fatty acids. Serum fatty acids including ΣSFA, ΣUFA, ΣMUFA, ΣPUFA did not significantly differ (P>0.05). Sheep fed with diet containing RPF had higher (P<0.05) n-3 PUFA as compared to control. The diets did not influence (P>0.05) the levels of ALT, ALP and AST but the concentrations of ALP and AST were affected by sampling day. There was no difference (P>0.05) in slaughter weight, hot and cold carcass weights, dressing percentage, chilling loss, rib eye area, non-carcass components, non-carcass fats, and primal cuts. However, back fat thickness was significantly affected among the treatments. Chemical composition of longissimus dorsi (LD) and semitendinosus (ST) muscles, meat cholesterol, meat pH, drip loss, cooking loss and shear force were not significantly affected. The muscle and liver metabolomics was conducted using 1H NMR spectroscopy. Six metabolites were identified from the muscle tissues including choline, creatine, glycerophosphocholine, inosine, isoleucine and lactate. The concentration of choline, creatine, glycerophosphocholine, inosine and lactate were significantly different but there was no significant difference observed in the concentration of isoleucine. The supplementation of prilled fat with lecithin (T3) decreased SFA and increased MUFA and PUFA in the meat. Also, it increased the concentrations of C18:1n-9, CLA Cis-9 Trans-11, CLA Trans-10 Cis-12, C18-2n-6, C18-3n-3 and reduced n-6:n-3 which is beneficial to human health making the meat from Dorper crossbred sheep, free from negative effect.